Implementation of alcohol and drug screening, brief intervention, and referral to treatment: Nurse practitioner learner perspectives on a mobile app. Issue 4 (April 2019) - Curtis, Alexa C.; Satre, Derek D.; Ly, Khanh; Wamsley, Maria; Satterfield, Jason
ABSTRACT: Background and purpose: Screening, brief Intervention, and referral to treatment (SBIRT) is a widely trained evidence-based strategy to identify and address alcohol and drug use problems. The purpose of this qualitative study was to explore the experience of family nurse practitioner (FNP) learners in the implementation of SBIRT and the perceived clinical utility of an SBIRT mobile app. Methods: Twenty-two FNP learners completed didactic SBIRT training and orientation to an SBIRT mobile app. At the conclusion of the study, participant focus groups explored overall SBIRT delivery (N = 19) and SBIRT mobile app utilization (N = 14). Focus group data were analyzed within a Theory of Planned Behavior framework. Results: Participants indicated that the mobile app was useful in the ongoing development of SBIRT knowledge, skill confidence, and motivation. Learners identified the clinical context as a major factor in facilitating the delivery of SBIRT overall. Participants who did not deliver SBIRT indicated that the most significant barriers to SBIRT implementation were lack of support from clinical preceptors and health systems. Conclusions: Findings suggest that a mobile app is an acceptable and feasible tool to improve the delivery of SBIRT. However, collaboration with preceptors and clinical training organizations is essential to optimize clinical translation.